1981
DOI: 10.1098/rspa.1981.0067
|View full text |Cite
|
Sign up to set email alerts
|

The oxidation of decane in the liquid and gaseous phases

Abstract: Studies have been made of the uncatalysed oxidation of decane in both the liquid and gaseous phases in the same temperature region; this hydrocarbon is probably the lowest molecular mass alkane for which such a direct comparison can be made. Although the mechanisms of oxidation in both phases are in many ways similar, some notable differences exist. The absence of C 10 O-heterocycles and the relatively high selectivity of initial attack of decane in the liquid phase can be ascribed to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

1984
1984
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 22 publications
2
1
0
Order By: Relevance
“…Similarly, all ketone isomers of C ini are formed and also all 2-ketones (from C 3 to C ini ). According to our results, the 2-ketones with C ini–1 are disfavored, in line with literature. , C ini ketones are qualitatively more produced than lighter ones. All aldehydes from C 1 to C ini are formed during n -alkanes autoxidation as well.…”
Section: Resultssupporting
confidence: 92%
“…Similarly, all ketone isomers of C ini are formed and also all 2-ketones (from C 3 to C ini ). According to our results, the 2-ketones with C ini–1 are disfavored, in line with literature. , C ini ketones are qualitatively more produced than lighter ones. All aldehydes from C 1 to C ini are formed during n -alkanes autoxidation as well.…”
Section: Resultssupporting
confidence: 92%
“…Table presents products identified by chemical family for all C 8 alkanes studied in the present work. These identifications are also confirmed with previous work. ,,, Except for the TMP, similar oxidation products were identified over the temperature range 373–433 K. TMP analyses did not reveal a significant amount of oxygenated species for the low temperature range (≤393 K), while both C 8 ketones and alcohols where observed at higher temperature (≥403 K). This tends to demonstrate two oxidation regimes of TMP respectively below 400 K and above 400 K in the absence of possible experimental bias for long IP measurements.…”
Section: Resultssupporting
confidence: 90%
“…There is a possibility that, instead of increased production from lipid peroxidation, oxidative stress resulted in autoxidation of these alkanes. This remains a relatively improbable reaction at body temperature, however, and would require free radical chain initiators or other catalysts [ 29 , 30 ]. Interestingly, studies with healthy volunteers have consistently found an association of oxygen exposure with an increase in various alkanes, methyl alkanes and aldehydes, although they remain heterogeneous in terms of specific VOCs found [ 8 , 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%